2021
DOI: 10.1049/ccs2.12022
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of instantaneous likeability of advertisements using deep learning

Abstract: The degree to which advertisements are successful is of prime concern for vendors in highly competitive global markets. Given the astounding growth of multimedia content on the internet, online marketing has become another form of advertising. Researchers consider advertisement likeability a major predictor of effective market penetration. An algorithm is presented to predict how much an advertisement clip will be liked with the aid of an end-to-end audiovisual feature extraction process using cognitive comput… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…The study found that entertainment, informativeness, and customization were the strongest positive drivers of purchase intention, and irritation negatively influenced purchase intention. To predict the instantaneous likeability of advertisements, Saha et al [29] proposed a prediction algorithm based on deep learning and compared it with other methods. The authors classified advertisement clips into five categories (i.e., entertaining, creative, emotional, humorous, and miscellaneous) based on the overall impression of raters.…”
Section: Previous Studies On Online Video Advertisementmentioning
confidence: 99%
See 1 more Smart Citation
“…The study found that entertainment, informativeness, and customization were the strongest positive drivers of purchase intention, and irritation negatively influenced purchase intention. To predict the instantaneous likeability of advertisements, Saha et al [29] proposed a prediction algorithm based on deep learning and compared it with other methods. The authors classified advertisement clips into five categories (i.e., entertaining, creative, emotional, humorous, and miscellaneous) based on the overall impression of raters.…”
Section: Previous Studies On Online Video Advertisementmentioning
confidence: 99%
“…In addition, most previous studies have used perception data through survey methods. Saha et al [29] proposed a prediction algorithm based on deep learning methods to predict the instantaneous likeability of an advertisement. However, they did not classify the advertisement into likeability factors from the perspective of viewers and validate them.…”
Section: Previous Studies On Online Video Advertisementmentioning
confidence: 99%